The Philosophy of Architecture. An epistemological approach to the design of space - Cristiá, Felix Alejandro (ARFIL y UNL, 2021)
The process of architectural design starts from a mental activity based on relations of abstract and empirical concepts prior to the materialization of what we know as built space and architecture. This process does not start in sketches or plans, but in the mind in advance through processes of imaginary relationships (synthesis) of concepts and analogies. The relationship between philosophy and architecture nowadays maybe is not as close as in ancient times, however, the understanding of this relationship becomes crucial in order to experience in the best possible way the spaces in which the human being grows, develops itself and produces his/her vision of world.